Feeding the Eternal City: Jewish and Christian Butchers in the Roman Ghetto - Stow, Kenneth R. (I Tatti Studies in Italian Renaissance History, 2024)
A surprising history of interfaith collaboration in the Roman Ghetto, where for three centuries Jewish and Christian butchers worked together to provision the city despite the proscriptions of Church law.For Rome’s Jewish population, confined to a ghetto between 1555 and 1870, efforts to secure kosher meat were fraught with challenges. The city’s papal authorities viewed kashrut—the Jewish dietary laws—with suspicion, and it was widely believed that kosher meat would contaminate any Christian who consumed it. Supplying kosher provisions entailed circumventing canon law and the institutions that regulated the butchering and sale of meat throughout the city.Kenneth Stow finds that Jewish butchers collaborated extensively with their Christian counterparts to ensure a supply of kosher meat, regardless of the laws that prohibited such interactions. Jewish butchers sold nonkosher portions of slaughtered animals daily to Christians outside the ghetto, which in turn ensured the affordability of kosher meat. At the same time, Christian butchers also found it profitable to work with Jews, as this enabled them to sell good meat otherwise unavailable at attractive prices. These relationships could be warm and almost intimate, but they could also be rife with anger, deception, and even litigation. Nonetheless, without this close cooperation—and the willingness of authorities to turn a blind eye to it—meat-eating in the ghetto would have been nearly impossible. Only the rise of the secular state in the late nineteenth century brought fundamental change, putting an end to canon law and allowing the kosher meat market to flourish.A rich social history of food in early modern Rome, Feeding the Eternal City is also a compelling narrative of Jewish life and religious acculturation in the capital of Catholicism